SERPINH1 functions as a multifunctional regulator to promote the malignant progression of cervical cancer. - Qian Liu; Yuanhao Peng; Wenbin Liu; Xiangjian Luo (PLoS ONE, 2025)
Cervical cancer remains the second leading cause of female cancer mortality worldwide, with metastasis representing a critical therapeutic challenge. This study systematically reveals the key role of SERPINH1 (Serpin Family H Member 1) as a hub regulator of malignant progression in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). Through analysis of TCGA-CESC datasets, we identified that high SERPINH1 expression is significantly correlated with poor prognosis and contributes to tumor progression by promoting cell proliferation, invasion, and metastatic phenotypes. In vitro experiments validated these findings, demonstrating that SERPINH1 overexpression markedly enhanced the proliferation, invasion, and metastasis of cervical cancer cells, whereas its knockdown substantially inhibited these processes. Furthermore, based on the SERPINH1-related differentially expressed genes, a prognostic risk model was constructed, successfully identifying PLOD1, ITGA5, and ESM1 as core collaborative genes affecting patient prognosis. Overall, our findings underscore the multiple functions of SERPINH1 as a hub for cervical cancer metastasis regulation, suggesting its potential as a promising biomarker for tailoring strategies in metastasis patients of CESC.